Studi Eksplorasi Kinerja Lulusan Program Studi Magister Pendidikan Dasar Universitas Negeri Jakarta - markus harefa; Nidya Chandra Muji Utami (Jurnal Elementaria Edukasia, 2023)
The Master of Basic Education Study Program, State University of Jakarta conducted a tracer study in meeting the demands of the market, especially the workforce and to increase competitiveness in improving the education system so far. Data were collected through the distribution of questionnaires given to alumni (graduates) from 2012 to 2022. Respondents of the tracer study consisted of 44 alumni of the Master of Basic Education Study Program, State University of Jakarta. Data analysis was carried out descriptively quantitatively in the form of percentages and the meaning of each tracer study finding was carried out qualitatively. The stages of interpreting tracer study data are data collection stages, data reduction stages, data exposure stages and data verification stages. The results of this tracer study are expected to be taken into consideration for policy makers in making improvements and updating educational strategies and orientations, making technical improvements to the implementation of education and teaching, and providing input for curriculum improvement / change so that graduates of the Master of Basic Education Study Program, State University of Jakarta become better in their intellectual capacity, skills and morals and personality.